2003
DOI: 10.1002/pdi.445
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an effective outpatient intensive education programme for patients with type 1 diabetes

Abstract: Education for our local clinic population with type 1 diabetes was unsatisfactory with an HbA 1c audit revealing suboptimal diabetes control. Clinical practice was changed to offer structured, group education to newly diagnosed and established patients with type 1 diabetes. Since 1999, 58 patients, 28 male, mean age 32 (range 18-65) years, mean duration of diabetes 2 (range 0.6-34) years have completed the programme.HbA 1c (mean±SE) fell from 8.9±0.2% to 8.4±0.2% (p<0.001) at three months, was maintained at si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…They aim to provide individuals who have diabetes with the relevant information and skills to better understand and manage their illness. Programmes such as DAFNE (Dose Adjustment for Normal Eating),48 BERTIE (Bournemouth Type 1 Intensive Education),49 X-PERT50 and DESMOND (Diabetes Education and Self-Management for Ongoing and Newly Diagnosed)51 have been designed in a culture of quality assurance and evidence-based practice and are delivered by committed, highly trained practitioners. Outcome studies have shown that these programmes impact on multiple outcomes including quality of life and promotion of self-care behaviours;48–51 however, demonstrable improvements in HbA 1c have proved to be elusive.…”
Section: Psychological and Educational Interventions To Improve Hba1cmentioning
confidence: 99%
“…They aim to provide individuals who have diabetes with the relevant information and skills to better understand and manage their illness. Programmes such as DAFNE (Dose Adjustment for Normal Eating),48 BERTIE (Bournemouth Type 1 Intensive Education),49 X-PERT50 and DESMOND (Diabetes Education and Self-Management for Ongoing and Newly Diagnosed)51 have been designed in a culture of quality assurance and evidence-based practice and are delivered by committed, highly trained practitioners. Outcome studies have shown that these programmes impact on multiple outcomes including quality of life and promotion of self-care behaviours;48–51 however, demonstrable improvements in HbA 1c have proved to be elusive.…”
Section: Psychological and Educational Interventions To Improve Hba1cmentioning
confidence: 99%
“…Both developed programmes based on the Düsseldorf programme, but delivered these differently. Everett et al describe their programme (BERTIE) in this issue of Practical Diabetes International 5 (see page 51) soon after the DAFNE study group published their initial research findings in the BMJ last year 6. Deirdre Kyne Grzebalski highlights the differences between the two programmes in her commentary accompanying the article (see page 44).…”
Section: Programme Challengesmentioning
confidence: 99%
“…Because the consequences of suboptimal glycaemic control are serious and potentially life‐threatening considerable resources have been invested in the development of structured diabetes educational (SDE) programmes for young people with Type 1 diabetes over the past two decades . Well‐established programmes include: DAFNE , which is delivered over five full days with a follow‐up session 2 months later; BERTIE , which involves attending a 6‐h group education programme once a week for four consecutive weeks; and the CHOICE programme which also runs 1 day a week for 4 weeks, and was specifically tailored to adolescents. At the time of the study, none of these courses are routinely held over a weekend or during the evening.…”
Section: Introductionmentioning
confidence: 99%
“…Because the consequences of suboptimal glycaemic control are serious and potentially life-threatening [5] considerable resources have been invested in the development of structured diabetes educational (SDE) programmes for young people with Type 1 diabetes over the past two decades [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation